2013
DOI: 10.1017/aee.2013.15
|View full text |Cite
|
Sign up to set email alerts
|

Supporting the Sustainability Journey of Tertiary International Students in Australia

Abstract: This article reports the findings of a pilot Education for Sustainability (EfS) program implemented in 2011 for international students in a multicampus distributed learning environment at an Australian university. It outlines the context of the pilot EfS program and reports survey findings of the environmental attitudes and sustainability worldviews of international students. The pilot EfS program entailed in-class presentations to students in a variety of Business and IT programs at diploma, undergraduate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
(44 reference statements)
3
8
0
Order By: Relevance
“…Instead, it revealed a convergence characterised by an increased sensitivity to environmental damage and a growing confidence in human ingenuity to overcome environmental limits or constraints. The finding concurred with the earlier pilot study (Sidiropoulos et al, 2013) and confirmed other research reporting a growing 'anthropocentric environmentalist' or 'utilitarian' view in students around the world (Bechtel et al, 2006;Corral-Verdugo et al, 2008;Dervisoglu, 2010;Erdogan, 2013;Erdoğan, 2009;Kuo and Jackson, 2014;Teisl et al, 2011), and particularly in developing/transitional economies.…”
Section: Discipline Of Studysupporting
confidence: 90%
See 2 more Smart Citations
“…Instead, it revealed a convergence characterised by an increased sensitivity to environmental damage and a growing confidence in human ingenuity to overcome environmental limits or constraints. The finding concurred with the earlier pilot study (Sidiropoulos et al, 2013) and confirmed other research reporting a growing 'anthropocentric environmentalist' or 'utilitarian' view in students around the world (Bechtel et al, 2006;Corral-Verdugo et al, 2008;Dervisoglu, 2010;Erdogan, 2013;Erdoğan, 2009;Kuo and Jackson, 2014;Teisl et al, 2011), and particularly in developing/transitional economies.…”
Section: Discipline Of Studysupporting
confidence: 90%
“…Cross-sectional and longitudinal analyses showed significant differences in pre-test as well as post-test NEP responses that varied by discipline of study and demographic factors, principally gender. In some studies, students held a weaker pro-ecological stance after completing regular courses (Harraway et al, 2012); other research revealed little or no changes in attitudes after sustainability education (Dagiliūtė and Liobikienė, 2015;Jowett et al, 2013;Mintz and Tal, 2013;Rideout, 2014;Yavetz et al, 2009); some reported a mixture of responses (Dagiliūtė and Niaura, 2014;Felgendreher and Löfgren, 2017;Fisher and McAdams, 2015;Sidiropoulos et al, 2013) while a few reported improved self-efficacy and self-reported behaviours (Mullenbach and Green, 2016;Sidiropoulos, 2014). More recent studies addressed several aspects of students' attitudes and behaviour, again with mixed results.…”
Section: Integration Of Sustainability In the Curriculummentioning
confidence: 99%
See 1 more Smart Citation
“…These include academic affiliation (major subject) [25,26], sex [26,27], age or year of studies [22,25], as well as formal and informal educational experiences [25,28]. Moreover, researchers argue that increasing students' understanding of sustainability concepts increases their PPR [21,29,30].…”
Section: Research On Perceived Professional Relevance (Ppr)mentioning
confidence: 99%
“…An obvious reason for pursuing tertiary education overseas is to learn and to experience cultural diversity at a university, which may not be available from the students' countries of origin [8]. University life in a foreign country provides an opportunity for an international student to live independently, and manage his/her own finance, lifestyle, personality and environment [4] [7] [9]. Studying abroad offers opportunities of promoting creative cognition and creative thinking through campus intercultural societies [10] [11].…”
Section: Internationalisation Of Tertiary Education In Australiamentioning
confidence: 99%